Clinical Decision-Making in Nursing Scale (CDMNS-PT©) in nursing students: Translation and validation - Duarte, Hugo Miguel Santos (2022)
to validate, for the Portuguese population, the Clinical Decision-Making Nursing Scale© (CDMNS©). Methods: this methodological study involved 496 nursing students who filled in a questionnaire created using sociodemographic and academic data, and the scale to evaluate the making of decisions in nursing. Results: the confirmatory factorial analysis showed that the adjustment of the factorial structure has good quality, being made up by three factors (X2/gl = 2.056; GFI = 0.927; CFI = 0.917; RMSEA = 0.046; RMR = 0.039; SRMR = 0.050). For the scale to be reliable, it had to include only the reliability of the scale required it to be constituted by 23 items, with correlation values that varied from 0.184 and 0.610, and a global Cronbach’s Alpha of 0.851, which showed its good reliability. Conclusions: the CDMNS-PT© is valid and reliable, showing a high potential to be used in clinical practice and investigation.